PENGARUH MODEL PAIR CHECKS TERHADAP KOMUNIKASI INTERPERSONAL MAHASISWA PGSD FKIP UMSU - Eko Febri Syahputra Siregar; Suci Perwita Sari (JURNAL TEMATIK, 2020)
This study aims to improve students' interpersonal communication skills in the Citizenship subject by using the Pair Checks model. This type of research is an experimental study with the subject of students in class II A as many as 25 people (experimental class) and class F as many as 25 people (control class). This research was conducted by giving actions in each class according to the planned model and then carried out measurements through a questionnaire to determine the interpersonal communication skills of students in each class. Based on the results of the study, the average results obtained by students 'interpersonal communication skills taught with the Pair Checks model (experimental class) of 95.72 and the average students' interpersonal communication skills taught with conventional models (control classes) of 90.88. So it can be concluded that students' interpersonal communication skills with the Pair Checks model are better than students who are taught with conventional models. Then based on the results of the t test, obtained t-sig (2-tailed) data of 0.007 (p <0.05) which shows that there are significant differences between the interpersonal communication abilities of students in the experimental class and the control class, so it can be concluded that there is an influence, Pair Checks model of PGSD student interpersonal communication in the Citizenship subject.